Can Antarctic fur seals be used to monitor sea temperature at South Georgia? - McCafferty, DJ; Boyd, Ian Lamont; Walker, TR; Taylor, RI (1999)
The breeding performance of higher predators has often been used to monitor fluctuations in the abundance of important prey stocks in marine ecosystems. The development of electronic data-loggers in recent years has also provided the opportunity of using wide-ranging marine animals to measure physical oceanographic conditions. In this study, time-depth recorders (TDRs) programmed to record temperature were deployed on female Antarctic fur seals (Arctocephalus gazella) at Bird Island, South Georgia (54 degrees 00'S; 38 degrees 02'W) during the breeding seasons 1994 to 1998. Temperature sensors had relatively slow response times, and thermal radiation errors occurred during the day when seals spent a large proportion of their time at the surface. Nevertheless, measurements provided temperature-depth profiles which were typical of the vertical stratification of the ocean. During the early stages of a foraging trip temperature increased, suggesting that fur seals travelled northwards from South Georgia towards the warmer waters of the Polar Front. In addition, higher temperatures were recorded by females that remained at sea for longer, implying that these individuals also travelled further. Mean sea-surface temperature (SST) increased from similar to 1 to 4 degrees C from December to March and agreed with SSTs from ship, buoy and satellite. Future studies on marine mammals which combine satellite tracking with oceanographic measurements are likely to provide valuable information on biophysical aspects of the ocean.